Inswing or Outswing Corner Kicks? A Meta-Analysis of Offensive Outcomes in Professional Soccer - Spyridon Plakias; Vasilis Armatas; Giannis Giakas (Journal of Coaching and Sports Science, 2025)
Background: Although corner kicks are the most tactically analyzed set pieces in professional soccer, there is still no consensus on whether inswinging or outswinging deliveries are more effective, and no previous meta-analysis has systematically addressed this question.Aims: The study aimed to compare the offensive effectiveness of inswinging and outswinging corner kicks, specifically concerning goal conversion and the creation of final attempts, while also examining differences between domestic and international competitions.Methods: A meta-analysis was conducted using data from 12 eligible studies involving professional competitions. Binary outcomes (goal vs. no goal; final attempt vs. no attempt) were analyzed using log odds ratios under a random-effects model to account for heterogeneity. Subgroup analyses were performed based on competition type (domestic vs. international).Result: The cumulative goal conversion rate from corners was 3.09%, while the rate for final attempts was 25.61%. No statistically significant difference was found between inswinging and outswinging corners regarding goal conversion (OR = 0.99, p = 0.67). However, outswinging corners increase the probability of a final attempt (OR = 0.79, p = 0.02) compared to inswinging corners.Conclusion:  This first meta-analysis comparing corner kick delivery types shows that, while both are equally effective for scoring, outswinging corners lead to more final attempts. Coaches may prioritize outswinging deliveries to improve offensive output and reduce counterattack risk. Future studies should examine contextual factors (e.g., marking systems, delivery zones) and include defensive outcomes for a more holistic tactical understanding.